2017
DOI: 10.2355/isijinternational.isijint-2016-573
|View full text |Cite
|
Sign up to set email alerts
|

Metal Emulsion in Sn Alloy/oxide System by Bottom Gas Injection

Abstract: A metal emulsion is formed by the passage of gas bubbles through the interface between the metal phase and the slag phase in the steelmaking process. Emulsified metal droplets have great potential to improve the chemical reaction efficiency during motion in bulk slag. Several studies have focused on the formation mechanism of metal droplets and on the influence of the physical properties of the system on this mechanism. In this study, Sn alloy and sodium tetraborate were used to simulate molten steel and slag,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Generally, room-temperature media such as water, oil, and mercury have been used to perform nondimensional analyses of liquid-liquid-gas systems [18]. Further, an additional rupture phenomenon wherein an elongated metal column is formed by two or three bubbles passing through the interface has also been reported in the case of a molten tin-molten salt system [19,20]. In this case, it was found that the liquid-liquid interfacial deformation behavior induced by a single rising bubble depends primarily on the physical properties of each liquid, such as density, viscosity, and interfacial tension.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, room-temperature media such as water, oil, and mercury have been used to perform nondimensional analyses of liquid-liquid-gas systems [18]. Further, an additional rupture phenomenon wherein an elongated metal column is formed by two or three bubbles passing through the interface has also been reported in the case of a molten tin-molten salt system [19,20]. In this case, it was found that the liquid-liquid interfacial deformation behavior induced by a single rising bubble depends primarily on the physical properties of each liquid, such as density, viscosity, and interfacial tension.…”
Section: Introductionmentioning
confidence: 99%